From Iceland to the Canary Islands: Understanding the Appeal of Mass Tourism in the Age of Over-Tourism - Kristín Loftsdóttir; Már Wolfgang Mixa (Tourism and Hospitality, 2025)
The Canary Islands have long been a major European destination for mass tourism, often associated with ‘sun-and-beach’ vacations. Critiques of mass tourism have intensified in recent years, as reflected in the 2024 protests in the Canary Islands, which linked mass tourism to economic inequalities and concerns about sustainability. Through the case example of Icelandic tourism to the Canary Islands, this research asks two questions: (a) why mass tourism destinations are appealing, and (b) how these reasons can be more fully understood within a broader geopolitical and structural context. The research methods include a survey conducted in Iceland in 2022 and an analysis of media coverage in Iceland related to the Canary Islands from 2017 to 2022. Survey data indicate that the islands are primarily perceived as an easily accessible, well-established holiday destination. Simultaneously, an analysis of media discussions reveals a limited discourse on the islands in Icelandic media, mainly focusing on tourism. The results illustrate how specific destinations become desirable by prioritizing infrastructure associated with mass tourism, where tourism’s impact on host communities, economies, and environments tends to be invisible.